GATA 3 Reactivity in Adenoid Cystic Carcinoma and Pleomorphic Adenoma of Salivary Glands - Ali Zaki NAJI; Ammar Eesa Mahdi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: The main targets is evaluate clinicopathological distribution and comparison of immunohistochemical (IHC) expression of GATA 3 between in adenoid cystic carcinoma (ACC) and pleomorphic adenoma (PA) of salivary . Design and Methods: This retrospective analysis, open surgical specimens of salivary gland that were done , and consisting of 150 cases that divided into three groups: normal salivary gland tissues (n=50), adenoid cystic carcinoma(n=50), and pleomorphic adenoma(n=50). Clinical data (age, sex, previous diseases ), physical examination, and investigations are done for all patients. In addition. These 150 cases of paraffin embedding blocks of salivary tissue were stained by ordinary stained (hematoxylin and eosin staining ). Manual IHC staining of GATA 3 was done. Results: Age groups is younger for normal salivary gland tissues than PA, and ACC . Sex distribution was slightly increase in male in comparison to female in normal salivary gland tissues and PA. GATA 3 staining was showing more positivity in normal salivary gland tissues (43/50 patients) than PA (27/50 patients) and ACC (14/50 patients). This positivity in GATA 3 IHC staining were more in male sex, regarding 55.8% in normal salivary gland tissues than ACC 50% and PA 51.9% . Age group 31-40, 40-50 and 61-70 years were showing more positive GATA 3 IHC staining in normal salivary gland tissues, PA, and ACC respectively. there was insignificant association between GATA 3 IHC staining with either age groups or sex groups distribution . Conclusion: GATA3 IHC is good marker and can used for searching salivary gland tumor origin, assisting in diagnosis Salivary gland tumors subtypes but GATA3 IHC staining has no association to specific sex or age groups in Salivary gland tumors. Usage of surgical operations for histopathological specimens preparation are better and give good efficiency for IHC markers staining.